Pemilihan bahasa dalam landskap linguistik di “Little India” Bandar Klang / Sathiaselan Arujanan - Sathiaselan, Arujanan (2017)
Malaysia is a multi-ethnic and multilingual nation where the majority of the population are Malays (68.6%), followed by the Chinese (23.2%), Indians (7%) and others (1.2%) (Department of Statistics Malaysia DOSM, 2017). The official language of Malaysia is called Bahasa Malaysia or Bahasa Melayu. Even though Bahasa Melayu is the official language, Article 152 (1) of the Constitution does not prohibit or impede the teaching and learning of minority languages such as Chinese and Tamil languages. The main language used among the Malaysian Indian community is Tamil. This is because majority of Indians living in Malaysia are the sub-ethnic Tamil. However, each sub-ethnic of the Indian community has different characteristics in terms of their language choice. In addition, the Malaysian multilingual situation also influences in the choice and use of different languages. The aim of this study is to examine the language choice of Indian businessmen in public space. Linguistic Landscape approach has been used as a framework to study the language choice on the signboards of business premises in "Little India", Klang city, Malaysia. Both quantitative and qualitative mixed methods were used to analyse the data collected. A total of 234 billboards images of business premises in "Little India", Klang city was collected and analysed by employing quantitative methodology. 3 randomly selected Indian traders were interviewed to obtain the qualitative data. This study shows that majority of the Indian traders prefer to use the English Language and Bahasa Malaysia on signboards at their business premises. Indian Businessman also use Tamil language on the signage in their business premises. The findings from the study shows that Malay language policy, the Local Council regulations and certain factors influenced the language choice of Indian businessmen in public space.